Moderating effect of market size in the relationship between political risk and foreign direct investment in Northern Nigeria - Koko, Musa Hatim (2017)
This study examined the geographical pattern of foreign investment in order to broadly explain the cumulative effect of two factors, namely political risk and market size on the foreign direct investment (FDI) into a country such as Nigeria, between the periods of 2000 to 2014. The objective is to assess the role of market size in mitigating the effect of political risk on FDI inflow in Northern Nigeria. Political risk indices which include kidnapping, investment profile, ethnic tension, religious tension, political violence, corruption and disputes with neighboring countries were adopted in order to assess the impact of political risk on FDI. Data analysis was conducted based on the time series data gathered from secondary panel sources. Simple linear regression analysis was used in estimating the effects of political risk on FDI and the role of regional, national and neighboring countries markets in reducing these effects. The results provided support to most of the hypothesized relationships proposed by this study. In this regard, the findings reveal that political risk is positively related to FDI at all levels of estimation. In addition, this study indicates that market size reduces the effect of political risk on FDI inflow at all three levels, namely Northern Nigeria, national market at large and neighboring countries markets. In essence, market size and growth in Nigeria is positive and promising enough in attracting FDI in the long run, as the disaggregated model shows that market size moderated the effect of political risk on FDI inflow significantly. Furthermore, this study through its dummy model found Boko Haram activities do not inhibit the inflow of FDI due to the market size effect. The finding on the moderator variable reveals its dual influencing ability, which is to mitigate the impact of political risk on FDI, as well as on market potentials and growth in Northern Nigeria and its neighboring countries. In conclusion, this study has basically highlights the significant effect of market size on the relationship between political risk and FDI in the Northern states of Nigeria. The results hopefully will encourage the marketing, promotion and security of the region, as it has potentials towards attracting inflow of FDI. Future research directions and managerial contributions related to market size, growth, political risk and FDI for the region are also discussed.